Meningkatkan Minat Mengenal Konsep Bilangan Melalui Metode Bermain Alat Manipulatif - Adella Kharisma Diyenti (Universitas Negeri Padang, 2021)
Studying the concept of number is part of the learning procedure of counting. Learning to count is one lesson that had to be given to early childhood. However, learning to count in early childhood. Ability to know the concept of numbers can be done in various ways packaged in an interesting and innovative, so as to foster interest in learning and teaching children to know the concept can be conveyed to the maximum number. One way meninggkatkan child's ability in the concept of number is a manipulative play, manipulative play is a play that involves hand eye coordination and motor skills. Children need the opportunity to work on a delicate skill that involves little more control and direction. Playing the manipulative develop a sense of coordination, challenging their little finger to follow the line or use their tools properly. To increase interest in learning mathematics to children in kindergartens. This study was performed in group A in kindergarten IT Ar-Rahmah